Potential use of oil palm trunk starch as coagulant and coagulant aid in semi-aerobic landfill leachate treatment - Y D Alazaiza, Motasem; Yusoff, Mohd Suffian; Aziz, Hamidi Abdul; Rui, Lo Ming (WA, 2019)
Landfill leachate is highly polluted wastewater and generated as a result of water infiltration through solid waste produced domestically and industrially. This study investigates the potential use of oil palm trunk starch (OPTS) and crosslinks oil palm trunk starch (C-OPTS) as coagulant and coagulant aid in tandem with polyaluminum chloride (PAC) for the treatment of landfill leachate. As primary coagulant, the optimum pH and dosage for OPTC were 7 and 500 mg/L, respectively. For C-OPTS, the optimum conditions were pH 8.3 and 1,000 mg/L C-OPTS dosage. However, the optimum conditions for PAC were pH 7 and 8,000 mg/L PAC dosage. Results show that OPTS demonstrated superior feasibility as a selective coagulant targeting heavy metals such as Mn (100% removal), Cu (95.6% removal), Zn (100% removal), and PO43- (100% removal), whereas C-OPTS can be employed as both bulk and selective coagulants. On the other hand, C-OPTS prevailed over PAC in Mn, Zn, PO43-, and chemical oxygen demand (COD) removals by huge margins of 100%, 54.8%, 24.3%, and 17.1%, respectively, without any pH adjustments and with optimum dosage 87.5% lower than that of PAC.
Keywords: coagulation-flocculation; landfill; oil palm trunk starch; semi-aerobic leachate